Multinational data show that conspiracy beliefs are associated with the perception (and reality) of poor national economic performance. (18th October 2022) - Hornsey, Matthew J.; Pearson, Samuel; Kang, Jemima; Sassenberg, Kai; Jetten, Jolanda; Van Lange, Paul A. M.; Medina, Lucia G.; Amiot, Catherine E.; Ausmees, Liisi; Baguma, Peter; Barry, Oumar; Becker, Maja; et al.
Abstract: While a great deal is known about the individual difference factors associated with conspiracy beliefs, much less is known about the country‐level factors that shape people's willingness to believe conspiracy theories. In the current article we discuss the possibility that willingness to believe conspiracy theories might be shaped by the perception (and reality) of poor economic performance at the national level. To test this notion, we surveyed 6723 participants from 36 countries. In line with predictions, propensity to believe conspiracy theories was negatively associated with perceptions of current and future national economic vitality. Furthermore, countries with higher GDP per capita tended to have lower belief in conspiracy theories. The data suggest that conspiracy beliefs are not just caused by intrapsychic factors but are also shaped by difficult economic circumstances for which distrust might have a rational basis.